Platelet reactivity changes significantly throughout all trimesters of pregnancy compared with the nonpregnant state: a prospective study. Issue 13 (7th August 2013) - Burke, N; Flood, K; Murray, A; Cotter, B; Dempsey, M; Fay, L; Dicker, P; Geary, MP; Kenny, D; Malone, FD
Abstract : Objective: Platelets play an important role in the pathophysiology of uteroplacental disease and platelet reactivity may be an important marker of uteroplacental disease activity. However, platelet reactivity has not been evaluated comprehensively in normal pregnancy. We sought to evaluate platelet reactivity using a number of agonists at defined time points in pregnancy using a novel platelet assay and compare these with a nonpregnant cohort. Design: Prospective longitudinal study. Setting: Outpatient department of a large tertiary referral centre. Sample: Eighty participants with 30 nonpregnant women and 50 pregnant women assessed longitudinally. Methods: This was a prospective cohort study performed longitudinally throughout uncomplicated singleton pregnancies with participants recruited before 15 weeks of gestation. They were controlled for a number of factors known to affect platelet reactivity. Blood samples were obtained in each trimester. Thirty nonpregnant healthy female volunteers also had a platelet assay performed. A modification of standard light transmission aggregometry was used to assess platelet function, with light absorbance measured following the addition of five different agonists at submaximal concentrations. Dose–response curves were plotted for each agonist for the nonpregnant cohort and in each trimester for the pregnant cohort. Main outcome measures: Dose–response curves and median effective concentration. Results: When compared with the nonpregnant controls a significant reduction was demonstrated in platelet reactivity to collagen during the first trimester of pregnancy ( P  < 0.0001). Platelet aggregation increased significantly from the first to third trimesters in response to collagen and arachidonic acid. Conclusion: Platelet reactivity varies according to pregnancy state, gestational age and agonist. The finding that platelet reactivity is reduced in the first trimester of pregnancy may be useful for the interpretation of further studies examining the role of platelet reactivity in the first trimester of pregnancies that develop uteroplacental disease.